До проблеми адміністративного позову - Картузова, Ірина Олексіївна; Картузова, Ирина Алексеевна; Kartuzova, Irina (My University, 2013)
This article is dedicated to the problem of administrative claim in administrative legal proceedings. The existing determinations of administrative claim have been investigated, the author's opinion about the notion, characteristics and devision of administrative claim has been stated.
Картузова І. О. До проблеми адміністративного позову / І. О. Картузова // Наукові праці Національного університету «Одеська юридична академія» : зб. наук. пр. / редкол.: С. В. Ківалов (голов. ред.), В. М. Дрьомін (заст. голов. ред.), Ю. П. Аленін [та ін.] ; відпов. за вип. В. М. Дрьомін ; МОН України, НУ ОЮА. – Одеса : Юрид. л-ра, 2013. – Т. 13. – С. 352-362.
Keywords: адміністративний позов; адміністративне судочинство; адміністративний суд; елементи адміністративного позову; види адміністративного позову; административный иск; административное судопроизводство; административный суд; элементы административного иска; виды административного иска; administrative claim; administrative legal proceedings; administrative court; elements of administrative claim; types of administrative claim